2011
DOI: 10.1007/s10495-011-0635-8
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin induces p53-dependent and -independent apoptogenic signaling in melanoma cells

Abstract: Various DNA-targeting agents may initiate p53-dependent as well as p53-independent response and subsequent apoptosis via alternative cellular systems which include for instance p73, caspase-2 or Bcl-2 family proteins. The scope of involvement of individual molecules in this process and the mechanisms governing their potential interplay are still not entirely understood, in particular in highly aggressive cancers such as in malignant melanoma. In this work we investigated the role and involvement of both p53-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Consistent with the stimulation of differentiation, there was reduced expression of Ki67 (Figure 6H) and of Keratin 7 (K7), a sebaceous lineage marker (Zouboulis et al., 1999) that is expressed in the SG basal layer (Ju et al., 2011) (Figure 6I). Conversely, when p53 activation in 4OHT-treated K14MycER mice was enhanced by daily application of camptothecin (a topoisomerase inhibitor that causes DNA breaks and activates p53 [Rudolf et al., 2011]) (Figures S5C–S5F), AR activity and proliferation in the SG lineage were reduced resulting in a reduction in gland size (Figure S5F). Testosterone coapplication partially antagonized the effects of camptothecin on the SG (Figures S5C–S5F).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the stimulation of differentiation, there was reduced expression of Ki67 (Figure 6H) and of Keratin 7 (K7), a sebaceous lineage marker (Zouboulis et al., 1999) that is expressed in the SG basal layer (Ju et al., 2011) (Figure 6I). Conversely, when p53 activation in 4OHT-treated K14MycER mice was enhanced by daily application of camptothecin (a topoisomerase inhibitor that causes DNA breaks and activates p53 [Rudolf et al., 2011]) (Figures S5C–S5F), AR activity and proliferation in the SG lineage were reduced resulting in a reduction in gland size (Figure S5F). Testosterone coapplication partially antagonized the effects of camptothecin on the SG (Figures S5C–S5F).…”
Section: Resultsmentioning
confidence: 99%
“…Here we show that treatment with ABT-888, at concentrations well below clinically achievable levels [10,12,13], sensitized both p53 wild type and mutant colon cancer cells lines to SN38 induced death in vitro. SN38, the active metabolite of irinotecan, is a potent topoisomerase I (topo 1) inhibitor that through its' interaction inhibits the separation of topo I from the DNA strand and can result in the formation of DSBs [40,41]. In healthy cells, this damage can be rapidly repaired via the major DNA damage repair pathways, HR and NHEJ.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TAp73 plays a role of tumour suppressive role in melanoma. In wild type p53-expressing melanoma cells, camptothecin, a cytotoxic quinoline alkaloid which inhibits the DNA enzyme topoisomerase I, induces p53-and p73-dependent apoptosis whereas in mutant p53-expressing melanoma cells, p73 and caspase-2 are predominantly involved in inducing apoptosis [63]. Recently, a study confirmed the involvement of TAp73 in inducing apoptosis in melanoma [64].…”
Section: Preventing Other Mechanisms From Inactivating P53mentioning
confidence: 99%